KAJIAN KETERSEDIAAN DAN KEBUTUHAN LAHAN TEMPAT PEMAKAMAN UMUM DI DISTRIK SARMI, KABUPATEN SARMI - Ronaldo Ruwayari, Daniel; Manalu, Janviter; Mujiati (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2025)
The availability and need for land for Public Cemeteries (TPU) is becoming an i ncreasingly urgent issue, especially in areas experiencing population growth such as Sarmi District, Sarmi Regency. This study aims to evaluate the current availability of TPU land, plan land use patterns in accordance with the Regional Spatial Plan (RTRW), and analyze local government involvement in TPU management. The research approach used is descriptive quantitative by utilizing primary and secondary data. Data collection techniques included field observations, interviews and analysis of policy documents. Data analysis was conducted using the Geographic Information System (GIS) method to identify alternative locations for new cemeteries and the geometric formula to project land requirements. The results show that TPU Mararena still has a land capacity of 1,434 m², while TPU Sarmi Kota has exhausted its capacity with a total area of 14,051 m². Projections of land requirements show the need for a new location with an area of around 10,000 m² to meet the needs of the cemetery in the long term. The new site needs to be designed based on spatial criteria, such as accessibility, integration of green spaces, and sustainability of management. This research emphasizes the importance of cross-sectoral coordination between local governments, communities and customary institutions to create more effective and environmentally friendly TPU management. New TPUs that support ecological, social, and aesthetic functions can be a sustainable solution to overcome the limitations of cemetery land in the future.